PENERAPAN MODEL KOOPERATIF TIPE STUDENTS TEAMS ACHIEVEMENT DIVISION (STAD) PADA SISWA SMA NEGERI 1 SUNGAI RAYA - Dwi Edi Budianto; Hairida Hairida; Ira Lestari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This study aimed to determine whether there is a significant difference between student learning outcomes given cooperative learning model type Students Teams Achievement Division (STAD) with students given conventional learning on the redox reaction material, the effect of cooperative learning model type Students Teams Achievement Division (STAD) ) in improving student learning outcomes and student responses to cooperative learning models of the Students Teams Achievement Division (STAD) type on redox reaction material. The form of research used was a quasi-experimental research design "Control Group Pre-test Post-test". Sampling used purposive sampling technique, and students of class XA were selected as experiment classes while XE as a control class. The data collection tools used in this study are student learning outcomes and student response questionnaires. The results of hypothesis testing used the Mann Whitney U-test with α of 5% obtained Z count (-5,11) ≤ -Z table (-1,96). This means that there was a significant difference between the learning outcomes of the control class students who were taught using the conventional method and the experimental class taught using a cooperative model of the Student Teams Achievement Division (STAD) type. Furthermore, based on the value of the Effect Size of 1.65 showed that cooperative learning type Student Teams Achievement Division has a high influence in improved the learning outcomes of class X students of SMA 1 Sungai Raya. Keywords: Students Teams Achievement Division, learning outcomes, student responses